Konsentrat Buah Naga Super Red (Hylocereus costaricensis) Sebagai Pewarna Alami dalam Pembuatan Permen Karet Sehat - Agnescia Clarissa Sera; Dwirina Hervilia (Politeknik Kesehatan Tanjung Karang, 2018)
In Indonesia, chewing gum is still classified as unhealthy snacks due to the content of synthetic dyes. These synthetic dyes can be replaced with natural dyes like anthocyanin and betacyanin, pigments found in super red dragon fruit (Hylocereus costaricensis). This research aimed to investigate color intensity and consumer preferences toward dragon fruit chewing gums and synthetic dyes-containing chewing gums. Five levels (80%, 70%, 60%, 50%, and 40%) of dragon fruits concentrations used as natural colorants and were compared to carmoisine, rose-pink, and purple synthetic dyes. Pure experimental research with the complete randomized design was employed. Color intensity (RGB value) was analyzed using Kruskal-Wallis statistical test (α 0.05). A total of 80 untrained panelists aged 17-30 years old evaluated the color of chewing gum. Level of panelist preferences was processed descriptively. There were significant color differences in red (p=0.037) and blue (p=0.012) in dragon fruit gum groups. There were significant differences between red (p=0.023), green (p=0.018) and blue (p=0.012) in synthetic-colored gum groups compared with 80% and 60% concentrate dragon fruit gums. The higher the percentage of the dragon fruit concentrate, the higher the intensity of color produced in chewing gums. Dragon fruit chewing gum with 80% concentration was preferable among other dragon fruit gum formulations. Carmoisine chewing gum produced sharper color intensity and was preferable among all products.